2015
DOI: 10.1111/wre.12168
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of loss of biodiversity associated with invasion by Chrysanthemoides monilifera subsp. monilifera (boneseed) across a large geographic region

Abstract: To investigate the impact of invasion by Chrysanthemoides monilifera ssp. monilifera (boneseed) on plant communities, sites that were invaded and uninvaded were surveyed across Tasmania, South Australia and Victoria, Australia. Above-ground cover abundance was estimated and samples of the seed bank from invaded and uninvaded sites in each state were collected and germinated in the glasshouse. We compared species richness and composition between invaded and uninvaded sites for both above-ground and belowground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This gradient was similar between boneseed and native shrub sites, one possibility is that the prevalence of boneseed throughout the study area may act to reduce canopy complexity. Such trends have been quantified previously, with boneseed infestation reducing the density of dominant undershrub and reducing the diversity of above-ground vegetation and the soil seedbank (French & Watts, 2015;Thomas et al, 2005). These processes could negatively impact wildlife species.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This gradient was similar between boneseed and native shrub sites, one possibility is that the prevalence of boneseed throughout the study area may act to reduce canopy complexity. Such trends have been quantified previously, with boneseed infestation reducing the density of dominant undershrub and reducing the diversity of above-ground vegetation and the soil seedbank (French & Watts, 2015;Thomas et al, 2005). These processes could negatively impact wildlife species.…”
Section: Discussionmentioning
confidence: 65%
“…was first introduced to Australia as an ornamental plant but has since spread and become a Weed of National Significance (Commonwealth of Australia, 2017). Boneseed impacts vegetation community composition and diversity and creates dense canopies limiting light infiltration (French & Watts, 2015;Thomas et al, 2005). It can support the increased establishment of other weeds (i.e., gorse Ulex europaeus) and decrease the standing biomass of native vegetation (French & Watts, 2015;McAlpine et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the synergistic effect or invasional meltdown hypothesis that emphasizes the positive role of exotic species in facilitating establishment and spread of other exotic species (Ricciardi, Hoopes, Marchetti, & Lockwood, ; Simberloff & Von Holle, ), our results indicate that H. persicum does not facilitate establishment of other exotic species. By reporting a high proportion of exotic invasive species co‐occurring with particularly dominant invasive species, several studies have supported the idea that exotic species facilitate each other's establishment, spread, and impact (e.g., French & Watts, ; Nielsen et al., ). However, our result does not support such an idea, as the other exotic species we found were overall few and scattered, and there was no difference in their occurrence between Heracleum invaded and noninvaded plots.…”
Section: Discussionmentioning
confidence: 99%
“…This study not only demonstrated the negative impacts of C. odorata on vegetation parameters, but also brought into fore some important plant indicators that can persist with its invasion (Figure 1). Most notable among these species is A. africana , a native weed species which has a similar growth form as C. odorata because it is likely that competitive exclusion is weak among species of similar growth forms (French & Watts, 2015) irrespective of their status (native or alien). The extent of the negative impact of C. odorata was also reflected in the high correlation between the importance value index of the invasive weed species and the invaded site.…”
Section: Discussionmentioning
confidence: 99%